Role of Pleural Biopsy in the Etiological Diagnosis of Exudative Pleural Effusion - Ahmed, Jamal Uddin; Hossain, Mohammad Delwar; Afroz, Farhana; Rahim, Muhammad Abdur; Musa, AKM (Bangladesh Critical Care Journal, 2017)
Purpose: Exudative pleural effusion usually indicates an underlying pulmonary pathology. Sometimes etiological diagnosis of exudative pleural effusion is difficult despite cytological, biochemical and microbiological tests. Aim of present study was to make an etiological diagnosis of exudative pleural effusion by pleural biopsy. Methods: This cross-sectional observational study was performed from January 2012 to December 2014 in the Department of Internal Medicine & Pulmonology of BIRDEM General Hospital, Dhaka, Bangladesh. A total of 51 patients with exudative pleural effusion in whom the diagnosis was uncertain after routine biochemical, cytological and microbiological evaluation of pleural fluid were included in the study. These patients underwent pleural biopsy by Abrams needle and histopathology was done to determine the etiology of pleural effusion. Results: Majority (74.5%) of the patients were male. Mean age of the patients was 52.7±16.0 years. Most (52.9%) patients had right sided pleural effusion. Histopathology report of the pleural biopsy showed granulomatous inflammation compatible with tuberculosis (TB) in 15 (29.4%), metastatic malignancy in 10 (19.6%) and chronic inflammation in 9 (17.6%) cases. In 17 (33.3%) cases the histopathology did not reveal any abnormality. Among 10 cases of metastatic malignancy, most (7, 70%) were adenocarcinoma. Compared to malignancy cases, TB cases were younger in age (Mean age: TB - 45.0±17.9 vs malignancy - 61.8±13.0 years). Pleural fluid was straw color in all (100%) cases of TB and hemorrhagic in almost all (90%) cases of metastatic malignancy (p 0.000). Mean value of pleural fluid protein (59.1±4.8 vs 47.3±4.2 gm/L; p 0.003), lactate dehydrogenase (LDH) (917.3±219.3 vs 464.3±112.3 U/L; p 0.101), adenosine deaminase (ADA) (39.0±3.7 vs 15.615.6±2.3 U/L; p 0.016), total leukocyte count (1039.3±776.8 vs 439.2±138.2 cells/cmm; p 0.328) and lymphocyte percentage (94.4±4.3 vs 68.3±9.3; p 0.003) were all raised in TB compared to metastatic malignancy Conclusions: Pleural biopsy was definitive diagnostic in almost half the patients with exudative pleural effusion. Tuberculosis was more common than malignancy particularly in young persons. Pleural fluid protein, LDH and ADA are significantly raised in TB compared to malignancy. Bangladesh Crit Care J March 2017; 5(1): 33-36